Ijarah-Based Commercial Transport and Its Relevance to Indonesian Law - Maarif, Muhamat Nur (Jurnal Ilmiah Dunia Hukum, 2025)
This study aims to examine the compatibility between the practices of commercial transportation services and the principles of ijarah contracts in Islamic law, as well as to assess their relevance to Indonesian statutory regulations, particularly Law Number 22 of 2009 concerning Road Traffic and Transportation. To achieve this objective, a normative-juridical research method was employed using a qualitative approach, supported by literature review of both classical and contemporary Islamic legal sources, alongside national positive law. The findings indicate that the core principles of the ijarah contract—such as clarity of the leased object (ma’qud ‘alayh), mutual consent (antarāḍin), and fairness in remuneration (ujrah)—are substantially reflected in the regulation of commercial transport services in Indonesia. However, several implementation aspects remain in need of reinforcement, especially those concerning safety responsibilities and the formulation of force majeure clauses, which do not yet fully reflect sharia values. Therefore, this study recommends the integration of maqāṣid al-sharī‘ah principles into the regulation of commercial transportation services to establish a more just, ethical, and sustainable transport system.